A randomized controlled trial on early induction compared to expectant management of nulliparous women with prolonged latent phases. (23rd July 2014) - Bräne, Elena; Olsson, Ann; Andolf, Ellika
Abstract Objective To compare early induction and expectant management regarding delivery outcomes and the experience of delivery in nulliparous women with prolonged latent phases. Design Randomized controlled trial. Setting One delivery unit in a Swedish hospital. Population Nulliparous women at term experiencing continuous contractions impeding rest (women's report) and exceeding 18 h, a cervical dilation of less than 4 cm, intact membranes and with a singleton fetus in cephalic presentation. Methods The women were randomly allocated to either early induction (n = 65) or expectant management (n = 64). All participants received medication for therapeutic rest. The early induction group was induced five hours after medication, and the expectant group awaited spontaneous onset of labor. The Wijma Delivery Experience Questionnaire (W‐DEQ version B) was filled in after delivery. Main outcome measures The primary outcome was mode of delivery. Secondary outcomes included birth experience, duration of labor, postpartum hemorrhage, and neonatal outcomes. Results The cesarean section rate was 15 of 65 (23.1%) in the early induction group and 24 of 64 (37.5%) in the expectant group (p = 0.076, OR 2.00, 95% CI 0.93–4.31). No significant differences were shown regarding delivery, neonatal outcomes or birth experience. Conclusions No significant differences were shown between the two groups in the rate of cesarean sections or the experience of delivery. According to the actual results, the power to detect a difference was only 45%. The cesarean section rate was high in both groups, regardless of intervention.